Potencial anticâncer de actinomicetos recuperados do sedimento da praia da Pedra Rachada, Paracuru, Ceará - Guimarães, Larissa Alves (2013)
The sea sediment is an important source of microorganisms that synthesize secondary metabolites with biomedical proprieties. During the past 10 years, the coast of Ceará has been prospected for the pharmacological potential housed in sponges, tunicates and corals, but little data are available regarding that of the microorganisms. In the present study, crude extracts from actinomycetes recovered from sediment collected at Pedra Rachada Beach, Paracuru, Ceará State, were evaluated for their cytotoxicity against tumor cells in culture. Among the 26 extracts, 16 inhibited more than 65% of growth of HCT-116 cells. The extract derived from the strain BRA-090, which exhibited the highest percentage of cell growth inhibition (98.38%), showed IC50 of 0.19 µg/mL and was grown in large scale in order to isolate active principles. Chemical fractionation techniques, such as flash chromatography and HPLC, were applied to this extract, which led to identification of three known chromomycins (chromomycins A2, A3 and desmetilchromomycin A2) and also two molecular masses regarding probable new molecules of the same class. Chromomycin A2 (C-A2) was isolated and the cytotoxic activity was evaluated across a panel of cell lines, with IC50 ranging from 7.8 to 49.5 nM for exposures of 48 and 72h. For 24h exposure period, none of the IC50 values were found to be below 50 nM. C-A2 was also tested against the non-tumor line MRC-5 with IC50 of 109 nM. The MALME-3M cells, which showed the best activity after 48h incubation, was chosen to investigate the potent cytotoxic effect of C-A2 at concentrations of 10, 20, 30 and 40 nM. C- A2 reduced viability of MALME-3M cells in concentration dependent manner and increased the number of non-viable cells in the two highest concentrations tested. As for changes in the cell cycle, C-A2 induced, particularly for treatment with 40 nM, reduction of S phase and increase in G0/G1 phase. Morphological analysis of MALME-3M cells treated with C-A2, mainly at 30 and 40 nM, presented membrane blebs, cellular volume reduction and DNA fragmentation, which are features suggestive of apoptosis. Treatment with 30 nM also induced the appearance of several cell fragments resembling autophagosomes, may suggest the occurrence of autophagy.